2021
DOI: 10.3390/jcm10235626
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic and Lockdown Restrictions on Cardiac Implantable Device Recipients with Remote Monitoring

Abstract: From 2020, many countries have adopted several restrictions to limit the COVID-19 pandemic. The forced containment impacted on healthcare organizations and the everyday life of patients with heart disease. We prospectively analyzed data recorded from implantable defibrillators and/or cardiac resynchronization devices of Italian patients during the lockdown (LDP), post-lockdown period (PLDP) and a control period (CP) of the previous year. We analyzed device data of the period 9 March 2019–31 May 2020 of remotel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[66][67][68][69][70][71][72][73][74][75][76][77]; not acute COVID-19 population-Refs. [78][79][80][81][82][83][84][85][86][87][88][89][90]; not in English or Italian-Refs. [49,50]; study design-Refs.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[66][67][68][69][70][71][72][73][74][75][76][77]; not acute COVID-19 population-Refs. [78][79][80][81][82][83][84][85][86][87][88][89][90]; not in English or Italian-Refs. [49,50]; study design-Refs.…”
Section: Study Selectionmentioning
confidence: 99%
“…Reports excluded: Not formal assessment of dysautonomia-Refs [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][49,50]…”
mentioning
confidence: 99%
“…A study from Italy, enrolling 696 patients with cardiac devices, reported on the effects of COVID-19 and demonstrated a significant increase in the burdens of ventricular tachycardia, associated with a decrease in physical activity and heart rate variability [ 76 ]. Considering the trend of reduced physical activity in subjects with post-COVID conditions, this phenomenon appears to be associated with a direct impact of the reduced physical activity on ventricular arrythmias [ 76 ].…”
Section: Ventricular Arrythmias and Sudden Cardiac Deathmentioning
confidence: 99%
“…A study from Italy, enrolling 696 patients with cardiac devices, reported on the effects of COVID-19 and demonstrated a significant increase in the burdens of ventricular tachycardia, associated with a decrease in physical activity and heart rate variability [ 76 ]. Considering the trend of reduced physical activity in subjects with post-COVID conditions, this phenomenon appears to be associated with a direct impact of the reduced physical activity on ventricular arrythmias [ 76 ]. Another multicenter trial studying 204 post-COVID patients in a 3-month follow-up after hospitalization detected mildly impaired right ventricular function and higher rates of ventricular arrhythmias compared with a control group [ 77 ].…”
Section: Ventricular Arrythmias and Sudden Cardiac Deathmentioning
confidence: 99%
“… 2 , 13 , 14 As a consequence, there was an acceleration in the development of telemedicine and the use of RM in order to follow cardiac patients at distance. 10 , 11 , 15–17 …”
Section: Rm and Covid-19 Pandemicmentioning
confidence: 99%